Investigating the impact of viral message appeal and message credibility on consumer attitude toward brand - Majid Esmaeilpour; Farshad Aram (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Background - Due to the rapid growth of the Internet and use of e-commerce in recent years, viral marketing has drawn the attention of manufacturing and service organizations. However, no research has been conducted to examine the impact of message appeal and message source credibility on consumers' attitude with mediating role of intellectual involvement of consumers and their risk taking level. Purpose - The aim of this study was to examine the impact of appeal and message source credibility on consumers' attitude with mediating role of consumers' intellectual involvement and their risk taking level. Design/methodology/approach - The population of this study includes consumers of mobile phones (Samsung, Sony, Nokia, LG and iPhone) in Bushehr city (Iran). As the population of the study is unlimited, 430 questionnaires were distributed using available sampling method, and 391 questionnaires were collected and analyzed. Using structural equation modeling, data were analyzed through smart PLS software. Findings -The results show that the appeal and credibility of the message source have impact on consumer attitudes toward the brand. It was also found that intellectual involvement of consumers plays the mediating role in the relationship between message appeal and consumer attitudes toward brand. In the relationship between message source credibility and customer attitude towards the brand, the level of risk taking of people has no mediating role. Research limitations/implications - Data collection tool was questionnaire in this study, and questionnaire has some disadvantages that can affect the results. Additionally, this study was conducted in Bushehr city (Iran). Therefore, we should be cautious in generalizing the findings. Originality/value - In this study, the effect of message appeal and message source credibility on consumer attitude to brand was examined. The risk taking level of consumer and his involvement level were considered as mediating variables.
Keywords: M31; M37; 330; Viral marketing; message appeal; message source credibility; consumer attitude; the level of intellectual involvement; the level of risk taking